Manipulation resolves non-trivial structure of corrole monolayer on Ag(111) - Tebi, Stefano; Aldahhak, Hazem; Serrano, Giulia; Schöfberger, Wolfgang; Rauls, Eva; Schmidt, Wolf Gero; Koch, Reinhold; Müllegger, Stefan (Nanotechnology)

A Bifunctional Electrocatalyst for Oxygen Evolution and Oxygen Reduction Reactions in Water - Schöfberger, Wolfgang; Faschinger, Felix; Chattopadhyay, Samir; Bhakta, Snehadri; Mondal, Biswajit; Elemans, Johannes A. A. W.; Müllegger, Stefan; Tebi, Stefano; Koch, Reinhold; Klappenberger, Florian; Paszkiewicz, Mateusz; Barth, Johannes V.; et al. (Angewandte Chemie International Edition)

Experimental and Theoretical High-Energy-Resolution X-ray Absorption Spectroscopy: Implications for the Investigation of the Entatic State - Vollmers, Nora Jenny; Müller, Patrick; Hoffmann, Alexander; Herres-Pawlis, Sonja; Rohrmüller, Martin; Schmidt, Wolf Gero; Gerstmann, Uwe; Bauer, Matthias (Inorganic Chemistry)

Optical response of the Cu2S2diamond core in Cu2II(NGuaS)2Cl2 - Witte, Matthias; Grimm-Lebsanft, Benjamin; Goos, Arne; Binder, Stephan; Rübhausen, Michael; Bernard, Martin; Neuba, Adam; Gorelsky, Serge; Gerstmann, Uwe; Henkel, Gerald; Schmidt, Wolf Gero; Herres-Pawlis, Sonja (Journal of Computational Chemistry)

Temperature-Dependent Hole Mobility and Its Limit in Crystal-Phase P3HT Calculated from First Principles - Lücke, Andreas; Ortmann, Frank; Panhans, Michel; Sanna, Simone; Rauls, Eva; Gerstmann, Uwe; Schmidt, Wolf Gero (The Journal of Physical Chemistry B)

Inhomogeneous and Homogeneous Line Broadening of Optical Spectra of PTCDA Molecules Adsorbed at Step Edges of Alkali Halide Surfaces - Paulheim, A.; Marquardt, C.; Aldahhak, Hazem; Rauls, E.; Schmidt, Wolf Gero; Sokolowski, M. (The Journal of Physical Chemistry C)

Rare-earth silicide thin films on the Si(111) surface - Sanna, S.; Dues, C.; Schmidt, Wolf Gero; Timmer, F.; Wollschläger, J.; Franz, M.; Appelfeller, S.; Dähne, M. (Physical Review B)

Density functional theory of the CuA-like Cu2S2 diamond core in Cu 2II(NGuaS)2Cl2 - Witte, M.; Gerstmann, Uwe; Neuba, Adam; Henkel, G.; Schmidt, Wolf Gero (Journal of Computational Chemistry)

Grand canonical Peierls transition in In/Si(111) - Jeckelmann, Eric; Sanna, Simone; Schmidt, Wolf Gero; Speiser, Eugen; Esser, Norbert (Physical Review B)

Surface vibrational Raman modes of In:Si(111)(4×1)and(8×2)nanowires - Speiser, E.; Esser, N.; Wippermann, S.; Schmidt, Wolf Gero (Physical Review B)

Atomic size effects studied by transport in single silicide nanowires - Miccoli, I.; Edler, F.; Pfnür, H.; Appelfeller, S.; Dähne, M.; Holtgrewe, K.; Sanna, S.; Schmidt, Wolf Gero; Tegenkamp, C. (Physical Review B)

Vibration eigenmodes of the Au-(5×2)/Si(111) surface studied by Raman spectroscopy and first-principles calculations - Liebhaber, M.; Halbig, B.; Bass, U.; Geurts, J.; Neufeld, Sergej; Sanna, S.; Schmidt, Wolf Gero; Speiser, E.; Räthel, J.; Chandola, S.; Esser, N. (Physical Review B)

Surface induced vibrational modes in the fluorescence spectra of PTCDA adsorbed on the KCl(100) and NaCl(100) surfaces - Paulheim, A.; Marquardt, C.; Sokolowski, M.; Hochheim, M.; Bredow, T.; Aldahhak, Hazem; Rauls, E.; Schmidt, Wolf Gero (Physical Chemistry Chemical Physics)
We report a combined experiment-theory study on low energy vibrational modes in fluorescence spectra of perylene-3,4,9,10-tetracarboxylic acid dianhydride (PTCDA) molecules.

Strain-induced quasi-one-dimensional rare-earth silicide structures on Si(111) - Timmer, F.; Oelke, R.; Dues, C.; Sanna, S.; Schmidt, Wolf Gero; Franz, M.; Appelfeller, S.; Dähne, M.; Wollschläger, J. (Physical Review B)

Two-dimensional symbiotic solitons and vortices in binary condensates with attractive cross-species interaction - Ma, Xuekai; Driben, Rodislav; Malomed, Boris A.; Meier, Torsten; Schumacher, Stefan (Scientific Reports)

All-optical tailoring of single-photon spectra in a quantum-dot microcavity system - Breddermann, D.; Heinze, D.; Binder, R.; Zrenner, Artur; Schumacher, Stefan (Physical Review B)
Semiconductor quantum-dot cavity systems are promising sources for solid-state-based on-demand generation of single photons for quantum communication. Commonly, the spectral characteristics of the emitted single photon are fixed by system properties such as electronic transition energies and spectral properties of the cavity. In the present work we study cavity-enhanced single-photon generation from the quantum-dot biexciton through a partly stimulated nondegenerate two-photon emission. We show that frequency and linewidth of the single photon can be fully controlled by the stimulating laser pulse, ultimately allowing for efficient all-optical spectral shaping of the single photon.

Polarization dependence of nonlinear wave mixing of spinor polaritons in semiconductor microcavities - Lewandowski, Przemyslaw; Lafont, Ombline; Baudin, Emmanuel; Chan, Chris K. P.; Leung, P. T.; Luk, Samuel M. H.; Galopin, Elisabeth; Lemaître, Aristide; Bloch, Jacqueline; Tignon, Jerome; Roussignol, Philippe; Kwong, N. H.; et al. (Physical Review B)

Experimental realization of a polariton beam amplifier - Niemietz, Dominik; Schmutzler, Johannes; Lewandowski, Przemyslaw; Winkler, Karol; Aßmann, Marc; Schumacher, Stefan; Brodbeck, Sebastian; Kamp, Martin; Schneider, Christian; Höfling, Sven; Bayer, Manfred (Physical Review B)

Dynamics of exciton-polaritons in discrete lattices under incoherent localized pumping - Yulin, A. V.; Chestnov, I. Yu.; Ma, X.; Schumacher, Stefan; Peschel, U.; Egorov, O. A. (Physical Review B)

Bay-Extended, Distorted Perylene Esters Showing Visible Luminescence after Ultraviolet Excitation: Photophysical and Electrochemical Analysis - Vollbrecht, Joachim; Wiebeler, Christian; Neuba, Adam; Bock, Harald; Schumacher, Stefan; Kitzerow, Heinz-Siegfried (The Journal of Physical Chemistry C)